2012
DOI: 10.1039/c2an35589b
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman spectroscopic detection of polycyclic aromatic hydrocarbons (PAHs) using a gold nanoparticles-modified alginate gel network

Abstract: This work aims at the development of a fast scanning method for organic pollutants with low-cost small Raman spectrometers. A gold nanoparticles-embedded alginate gel is prepared and applied as the substrate for surface enhanced Raman spectrometric detection of polycyclic aromatic hydrocarbons (PAHs). The target molecules are captured by the three-dimensional network of the alginate gel, and brought close to the hot spots generated by gold nanoparticles embedded in the gel. Significant Raman enhancement effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…However, some obvious discrepancies have been observed. For example, the 1419 and 1634 cm À1 peaks of BaP reported by Bao et al [6] have shifted to 1428 and 1619 cm À1 , respectively. The 415, 742, and 1611 cm À1 of F are found at 429, 729, and 1600 cm À1 in this study, and the previously reported 1401 cm À1 peak of F and 492 cm À1 peak of ANT cannot be identified in our experiments.…”
Section: Sers Spectra Of Selected Pahsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some obvious discrepancies have been observed. For example, the 1419 and 1634 cm À1 peaks of BaP reported by Bao et al [6] have shifted to 1428 and 1619 cm À1 , respectively. The 415, 742, and 1611 cm À1 of F are found at 429, 729, and 1600 cm À1 in this study, and the previously reported 1401 cm À1 peak of F and 492 cm À1 peak of ANT cannot be identified in our experiments.…”
Section: Sers Spectra Of Selected Pahsmentioning
confidence: 99%
“…Hexanethiol, [40] decanethiol, [16] calix [4]arene, [19] cyclodextrin derivatives, [15] per-6-deoxy-(6-thio)-β-cyclodextrin (CD-SH), [41] and humic acids [17,20] have been reported, with the LODs ranging from 10 À5 to 10 À6 μg/ml. Novel SERS substrates with ultra-high enhancement factors, such as Au on TiO 2 nanotube arrays [42] and AuNPs on alginate gel, [6] have been proposed in PAH detection as well, and LODs could reach as low as 0.365 nM for BaP (equivalent to 9.2 × 10 À5 μg/ml). However, in these studies, SERS substrates were often soaked in the PAH solution for a certain period of time (e.g.…”
Section: Limits Of Detection (Lods) Of Pahs In Methanol Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al prepared a gold NPs-embedded alginate gel for the detection of PAHs and found that the targets were captured by the three-dimensional network and brought close to the hot spots generated by the nanoparticles embedded in the gel, leading to significant SERS enhancement [80]. Using this substrate, quantitative analysis of four PAHs such as benzo(a)pyrene was realized with LODs as low as to 0.365 nmol L −1 [81]. By making use of the collapse and recover ability of the hydrogel upon drying and rehydrated, the hydrogel-based substrate can also act as excellent mechanical molecular trap for the SERS detection.…”
Section: Hydrogel-based Substrate For Target Gatheringmentioning
confidence: 99%
“…Novel SERS substrates with ultra-high enhancement factors, such as Au coffee ring [14], Au on nickel 3D foam [15], Au on TiO 2 nanotube arrays [16], Au NPs on porous polymer [17], Ag nanoparticle islands with a SiO 2 spacer layer [18], and Au NPs on alginate gel [19], have been proposed for PAH detection. In most previous reports, a stringent and complicated protocol is a prerequisite for the successful synthesis of substrates, and the substrates were tailored for detecting a specific class of PAHs.…”
Section: Introductionmentioning
confidence: 99%